Sensitivitas dan spesifisitas food consumption score dalam mengidentifikasi rawan pangan dengan parameter status gizi balita - Firna, Aklesta Leni; Bambang, Azis Nur; Afifah, Diana Nur (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2018)
Background : Food consumption score (FCS) was one of indicators to measure the food insecurity that included some elements from food access and food consumption, but the sensitivity was different in each area so it was needed to do the sensitivity and specificity tests with the high precision and accuracy of parameter. Objectives : To do the sensitivity and specificity test of food consumption score to identify the food insecurity with parameter status of toddlers’ nutrition anthropometrically. Methods : Cross sectional study with total subjects 517 toddlers. Status of toddlers’ nutrition was counted according to zscore WHZ, WAZ, and HAZ. The FCS score was counted according to WFP formula. Results : Sensitivity (Se) and specificity (Sp) FCS test with parameter of WHZ, WAZ, HAZ as followed Se=0 Sp= ≥ 90%. Conclusion: The cut-off point of FCS that was set by WFP was non-sensitive in identifying the food insecurity with parameter status of toddlers’ nutrition.